2-Styrylquinoline-based two-photon AIEgens for dual monitoring of pH and viscosity in living cells. Issue 48 (22nd November 2019) - Dou, Yandong; Kenry,; Liu, Jiang; Zhang, Fangfang; Cai, Chunhui; Zhu, Qing
Abstract : A new class of aggregation-induced emission (AIE) fluorophores HAPHs with excellent two-photon properties is developed from styrylquinoline. Abstract : A new class of aggregation-induced emission (AIE) fluorophores HAPHs with excellent two-photon properties is developed from styrylquinoline. Among them, the probe HAPH-1 exhibits good sensitivity towards pH and viscosity and has been successfully used for simultaneous pH and viscosity detection in living cells through two-photon microscopy.